Self-Assembly System Based on Cyclodextrin for Targeted Delivery of Cannabidiol - Zhu, Panyong; Lv, Pin; Zhang, Yazhou; Liao, Rongqiang; Liu, Jing; Guo, Rong; Chen, Xuan; Liao, Xiali; Gao, Chuanzhu; Zhang, Kun; Yang, Ming; Yang, Bo (Frontiers in Chemistry, 2021)
Cannabidiol (CBD) is one peculiar kind of the cannabinoid in Cannabis sativa L with wide pharmacological activities. However, the poor water solubility and specificity of CBD limiting its application in pharmaceutical field. For solving these problems, in this work, we successfully prepared a targeted carrier by grafting biotin (BIO) onto ethylenediamine-β-Cyclodextrin (EN-CD) in a single step to generate a supramolecular biopolymer, named BIO-CD. Amantadine-conjugated cannabinoids (AD-CBD) was prepared and self-assembled with BIO-CD. At the same time, a series of methods were used to characterize the inclusion behavior and physicochemical properties of AD-CBD and BIO-CD. The results shown that AD-CBD entered the cavity of BIO-CD and formed a 1 : 1 host-guest inclusion complex. The possible inclusion mode of them was also speculated. MTT assay revealed that the targeting effect and confocal laser scanning microscopy (CLSM), anticancer activity of AD-CBD/BIO-CD inclusion complex against three human cancer cell lines were higher than BIO-CD, AD-CBD and free CBD. Moreover, the inclusion complex could release drugs under weakly acidic conditions. These convincingly results demonstrated that AD-CBD/BIO-CD inclusion complex possess excellent targeted and anticancer activity, which is hopeful to be applied to clinically as a new therapeutic approach.